Pengaruh Terpaan Berita Covid-19 Pada LINE Today Terhadap Kecemasan Mahasiswa Universitas Udayana - Puspita Rini, Ni Putu Yulia; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2021)
LINE Today in December 2019 was filled with news about Covid-19. Covid-19 is an infectious disease caused by a new type of coronavirus. Anxiety is an unpleasant emotional state characterized by feelings of fear, worry, and confusion. The purpose of this study was to explain the effect of exposure tonews Covid-19 on LINE Today on the anxiety of Udayana University students. This research was conducted on students at Udayana University. The sample of this study was 192 using non-probability sampling technique, namely purposive sampling. Collecting data through interview techniques and distributing digital questionnaires via google form. The analysis technique used is simple linear regression. TheNews Covid-19 Exposure on LINE Today has a positive and significant impact on Udayana University Student Anxiety. When the News Covid-19 Exposure on LINE Today increases, the Anxiety of Udayana University students will increase as well.   Keywords: News Covid-19 Exposure, LINE Today, Student Anxiety